Brief research report: Effects of Pinch deficiency on cartilage homeostasis in adult mice - Wu, Xiaohao; Lin, Sixiong; Liao, Rongdong; Yao, Qing; Lin, Lijun; Zou, Xuenong; Xiao, Guozhi (Frontiers in Cell and Developmental Biology, 2023)
Pinch1 and Pinch2 are LIM domain-containing proteins with crucial functions in mediating focal adhesion formation. Our previous studies have demonstrated that Pinch1/2 expression is essential for cartilage and bone formation during skeletal development in mice. Loss of Pinch expression (Prx1Cre; Pinch1flox/flox; Pinch2−/−) inhibits chondrocyte proliferation and promotes chondrocyte apoptosis, resulting in severe chondrodysplasia and limb shortening. Based on these observations, we wonder if Pinch proteins have a role in adult cartilage and whether Pinch deficiency will compromise cartilage homeostasis and promote osteoarthritis (OA)-related defects in adult mice. To this end, we generated the AggrecanCreERT2; Pinch1flox/flox; Pinch2−/− mice, in which the Pinch1 gene can be inducibly deleted in aggrecan-expressing chondrocytes by tamoxifen and the Pinch2 gene is globally inactivated. Immunofluorescent staining confirmed that the expression of Pinch proteins was significantly decreased in articular cartilage in tamoxifen-treated adult AggrecanCreERT2; Pinch1flox/flox; Pinch2−/− mice. Unexpectedly, our results showed that Pinch loss did not induce marked abnormalities in articular cartilage and other joint tissues in the knee joints of either adult (10-month-old) mice or aged (17-month-old) mice. In a destabilization of the medial meniscus (DMM)-induced OA model, the surgically-induced OA lesions were comparable between Pinch-deficient mice and control mice. Given the fact that Pinch proteins are essential for chondrogenesis and cartilage formation during skeletal development, these findings suggest that Pinch expression is seemingly not indispensable for adult cartilage homeostasis in mice.